Chapter La normalizzazione del lessico artistico francese: il «dizionario» di Félibien - CETRO, ROSA (Proceedings e report, 2021)
During the reign of Louis XIV, the figurative arts serve the royal propaganda and glorification of the sovereign. The essay Des Principes de l'Architecture, de la Sculpture et de la Peinture (1676) was written by the historian André Félibien with the aim of describing arts during the Grand Siècle. This essay contains one of the first specialised dictionaries on artistic lexicon. In this article, we aim to analyse the structure and contents of the dictionary (nomenclature, syntactic and semantic categories, definitions, specialised marks). Moreover, we will focus on the preface of the essay, in which the author describes the difficulties encountered in the terminological description of the artistic domain.